THE CHALLENGE OF FINANCIAL INCLUSION FOR SMALL AND MICRO ENTREPRISES IN INDONESIA - Suryani, Tatik; L,; Iramani, Rr. (PEOPLE: International Journal of Social Sciences, 2015)
Small and Micro Enterprises (SMEs) in Indonesia have many problems for growing and gaining competitive advantage. The main cause of the problem is that they are unable to access financial institutions, specifically banking. This research objective is to explore financial inclusion for among SMEs’ financial behavior perspective and their challenges. Research involved SME owners who produce local nominated products. By using depth interview, questionnaire and triangulation methods, the results show that most SMEs are lack of knowledge on banking product and services, besides the high rate of interest has made them to choose banks as sources of fund. Due to insufficiency of knowledge and experience led them reluctant to use banking products and services. The availability of bank branches around SMEs area, their unfamiliarity with technology, the unavailability of financial reporting documents and collateral have led them prefer personal loan to bank loan. Personal loan is considered a simple way of getting financing. Based on these findings it means that government as the regulator should educate them to about banking and financial capability and encourage bank not only to give credit but also assist them to manage their financial properly.